Pemanfaatan Museum Sumpah Pemuda sebagai Sumber Belajar melalui Teknologi Virtual Reality - Muhammad Afif Maghfur; Shafa Audilla R; Shofyan Fatkhurrohman; Tyara Priyanidya Y; Wahyo Setyoning (IAIN Salatiga, 2023)
This research aims to explore the utilization of the Youth Pledge Museum as a learning resource through Virtual Reality (VR) or Virtual Tour technology, and to understand the process of using VR in history education. The research adopts a qualitative method with a phenomenological approach. The focus of the study includes three main components: 1) Museum collections and their management, 2) The process of utilizing the Youth Pledge Museum collections as a source of historical learning through VR technology, and 3) The role of teachers in history education through VR technology. Data for the research were collected through observation, semi-structured interviews, and document analysis related to the Youth Pledge Museum and the use of VR in history education. This article describes the various collections held by the Youth Pledge Museum and the technologies that have been developed, including Virtual Reality (VR), which can be used in history education. The steps for using VR in history education include: 1) Selecting a relevant Virtual Reality museum for the learning material, 2) Preparing the necessary applications and equipment, 3) Setting up an Android phone, 4) Ensuring internet connectivity, 5) Finding the link to the Virtual Reality content of the Youth Pledge Museum, 6) Accessing the discovered link and starting the Virtual Tour. As a form of technology-integrated learning, the use of VR is expected to accommodate the development of 21st-century skills and encourage students to become active learners. This approach aligns with the student-centered learning concept applied in the independent curriculum, allowing students to construct their own knowledge.Keywords: museums, youth pledges, learning resources, Virtual Reality.